Islamic Boarding School Communication Strategy In Increasing Society Religious Understanding - Handayani, Nourma; Pratama, Ferly (UIN Fatmawati Sukarno Bengkulu, 2024)
The presence of Islamic boarding schools is the hope of the community, especially in non-urban areas. This hope becomes a mission for Islamic boarding schools in an effort to increase religious understanding, which requires certain methods or strategies for maximum results. This research seeks to analyze the communication strategies used by the Al-Ikhlas Islamic boarding school in Lahat district (South Sumatra) in the Tanjung Sakti Pumi sub-district in increasing the community's religious understanding, as well as trying to review what are the supporting and inhibiting factors for this communication strategy. The research method used is a descriptive method with data analysis techniques using Miles and Huberman interactive techniques. The research results show that the strategy is examined from the implementation of the communication strategy stages which are theoretically oriented: a) Getting to know the audience by visiting the community directly to find out their background and psychology. b) adapting material that is easily accepted and understood by the public. c) from the method aspect, the Al-Ikhlas Islamic boarding school uses the lecture method and question and answer method. d) from the media aspect used by the Al-Ikhlas Islamic boarding school, it is electronic and non-electronic media.